Point: Proposing the Electrokinetic Model. Issue 1 (January 2015) - Moeller, Marcus J.; Kuppe, Christoph
It is still not fully resolved how the glomerular filter works and why it never clogs. Several models have been proposed. In this review, we will compare the most widely used "pore model" to the more recent and refined "electrokinetic model" of glomerular filtration. The pore model assumes the existence of highly ordered regular pores, but it cannot provide a mechanistic explanation for several of the inherent characteristics of the glomerular filter. The electrokinetic model assumes that streaming potentials generate an electrical field along the filter surface which repels the negatively charged plasma proteins, preventing them from passing across the filter. The electrokinetic model can provide elegant mechanistic solutions for most of the unresolved riddles about the glomerular filter.